Uncoupling the Vicious Cycle of Mechanical Stress and Inflammation in Calcific Aortic Valve Disease - Dayawansa, Nalin H.; Baratchi, Sara; Peter, Karlheinz (Frontiers in Cardiovascular Medicine, 2022)
Calcific aortic valve disease (CAVD) is a common acquired valvulopathy, which carries a high burden of mortality. Chronic inflammation has been postulated as the predominant pathophysiological process underlying CAVD. So far, no effective medical therapies exist to halt the progression of CAVD. This review aims to outline the known pathways of inflammation and calcification in CAVD, focussing on the critical roles of mechanical stress and mechanosensing in the perpetuation of valvular inflammation. Following initiation of valvular inflammation, dysregulation of proinflammatory and osteoregulatory signalling pathways stimulates endothelial-mesenchymal transition of valvular endothelial cells (VECs) and differentiation of valvular interstitial cells (VICs) into active myofibroblastic and osteoblastic phenotypes, which in turn mediate valvular extracellular matrix remodelling and calcification. Mechanosensitive signalling pathways convert mechanical forces experienced by valve leaflets and circulating cells into biochemical signals and may provide the positive feedback loop that promotes acceleration of disease progression in the advanced stages of CAVD. Mechanosensing is implicated in multiple aspects of CAVD pathophysiology. The mechanosensitive RhoA/ROCK and YAP/TAZ systems are implicated in aortic valve leaflet mineralisation in response to increased substrate stiffness. Exposure of aortic valve leaflets, endothelial cells and platelets to high shear stress results in increased expression of mediators of VIC differentiation. Upregulation of the Piezo1 mechanoreceptor has been demonstrated to promote inflammation in CAVD, which normalises following transcatheter valve replacement. Genetic variants and inhibition of Notch signalling accentuate VIC responses to altered mechanical stresses. The study of mechanosensing pathways has revealed promising insights into the mechanisms that perpetuate inflammation and calcification in CAVD. Mechanotransduction of altered mechanical stresses may provide the sought-after coupling link that drives a vicious cycle of chronic inflammation in CAVD. Mechanosensing pathways may yield promising targets for therapeutic interventions and prognostic biomarkers with the potential to improve the management of CAVD.